The Writing process : composition and applied grammar - Olson, Miles C. (Boston : Allyn and Bacon, 1982)
Contents.--v.1 Book 7.--v.2. Book 8.--v.3. Book 9.--v.4. Book 10.-- v.5. Book 11.--v.6. Book 12.
Keywords: English language -- Composition and exercises